Early Oral Feeding versus Delayed Oral Feeding in Patients following Total Laryngectomy: A Systematic Review. (2nd September 2014) - Hay, Ashley; Pitkin, Lisa; Mathew, Rajeev; Gurusamy, Kurinchi
Abstract : Objectives: Assess the effects of early oral feeding in laryngectomy patients (before 7 days) versus delayed or late oral feeding (7 days or later). Methods: We considered randomized controlled trials (RCTs) irrespective of the use of blinding, language status, date of publication, setting, or sample sizes. The outcomes used were mortality, pharyngo‐cutaneous fistula rate, quality of life, hospital length of stay, and complications. To improve harmful effect estimates, trials with early oral feeding groups and a control group were also considered. We analyzed the data with fixed effect and random effect models and present the rate ratios, risk ratio, or mean difference. Results: We included 4 RCTs and 3 case controlled trials with 393 participants for assessment of harmful effects. The risk of bias in all trials was high. There was no statistically significant difference detected in mortality rates at 6 months, pharyngo‐cutaneous fistula rate, or complications between intervention and control groups. There was no data on quality of life. The length of hospital stay was shorter in the intervention early feeding group, mean difference effect estimate and confidence intervals using fixed effect model –2.72 [–5.34, –0.09] in favor of early oral feeding. Conclusions: The low quality of evidence does not support a change in practice. However, in an appropriate selected patient group early oral feeding has been used and there has been no detectable difference in mortality or complication rates. A shorter hospital stay was seen but was supported by limited evidence.